Diabetic foot exercise training for diabetes mellitus patients to control blood glucose during the COVID-19 pandemic - Arina Qona'ah; Anestasia Pangestu Mei Tyas; Andri Setiya Wahyudi; Amellia Mardhika (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Physical activity restriction during the pandemic increases the risk of developing diabetic foot ulcers in patients with diabetes mellitus. Community service activities in the form of diabetic foot exercise training aim to increase knowledge and blood glucose control of diabetic mellitus patients' during the pandemic. The activities were carried out in the Tlogorejo and Madulegi villages in Sukodadi Primary Health Care for 60 patients with diabetes mellitus who are members of prolanis. Community service activities include health education about diabetes and foot care, foot exercise training and physical examination, and fasting blood glucose testing. Post-test results showed that 80% of the participants had good knowledge, 15% had sufficient knowledge, and 5% lacked knowledge. Most participants could do foot exercises, and the average fasting blood glucose level of the participants after being given counseling and training was 171.60 mg/dL. Foot exercise training can increase participants' knowledge and can be used as a way to control blood glucose during the COVID-19 pandemic.